Experience of Application of GOST R 59638-2021 for the Analysis of Statistics of False Alarms of the Fire Alarm System on the Example of a Multifunctional Shopping and Entertainment Complex - D. A. Siksimov; V. E. Merenyashev (Безопасность техногенных и природных систем, 2022)
Introduction. In 2021, new regulatory legal acts in the field of fire safety came into force. Special attention is paid to the control, classification and minimization of false alarms of fire protection systems and installations. In this regard, it makes sense to refer to the statistics of such triggers on specific objects in order to assess the sufficiency and validity of the criteria proposed in the new documents. The purpose of the work is to study the requirements for maintenance and operation of fire protection systems and installations. The objectives of this study are to study the main approaches to the regulation of false alarms of fire protection systems, analysis of the main quantitative indicators of the operation of systems of a particular object, assessment of the compliance of the protection object with new requirements.Materials and Methods. The empirical basis of the study was the results of constant monitoring of the state of fire protection systems and installations in one of the largest shopping and entertainment complexes in the South of Russia. The reports of the fire prevention service, data from the automated workplace of the operator of the fire station, records in operational logs were used. The information is summarized in tables by types of false alarms and by chronology. Calculations were performed in MS Excel. To identify the links between different types of false positives, a correlation analysis was carried out.Results. The connection between the number of false alarms and the intensity of work of tenants of the protection object is noted. The ratios of different types of false alarm and the significance of the triggering factors are determined. The correlation between false alarms and malfunctions of systems is revealed.Discussion and Conclusion. The methodology developed by the authors makes it possible to monitor malfunctions of fire alarm systems on an ongoing basis. A number of problematic issues of applying the classification of false alarms of the fire alarm system in GOST R 59638-2021 have been identified. A connection has been established between the number of false alarms and the intensity of the work of the tenants of the shopping center. The conclusion is made about the compliance of the protection object with the newly introduced requirements. The identified problematic issues of the application of GOST R 59638-2021 for statistical analysis in future studies force us to develop a different classification of false alarms of fire alarm systems.